Evaluation of the Implementation of Traffic on the Road in the School Safe Zone (ZoSS) in Depok - Aswanti Setyawati; Mustika Sari; Sonya Sidjabat (Institut Transportasi dan Logistik Trisakti, 2021)
The implementation of the School Safe Zone (ZoSS) provision program in the Depok City area for early childhood education, basic education and education that has not been implemented optimally is in accordance with the objectives of implementing the ZoSS program. The purpose of this research is to increase traffic awareness in the area to school, where many parents, teachers and children do not care about good driving and care for the safety of themselves and others. The problem in this study is the lack of public awareness of how to get to the school area safely. The research method uses descriptive qualitative data collection methods by interviewing children who go to school in Depok and secondary data from journals. The results showed that the application of ZoSS in the city of Depok has been implemented with priority in 7 elementary schools (SD) with traffic signs and officers optimally.